Designing of a Multi-Microcontroller Hardware Platform for Academic Environment:The UMP-EVT - Selvakumar, Raja Saravana Kumar; Kamarul Hawari, Ghazali; Nik Mohd Kamil, Nik Yusof (2010)
In traditional Embedded Control Technology courses, students learn to develop assembly language programs to control peripherals, handle interrupts, and perform I/O operations. However, students find the subject are diffcult as the subject is presented in a lecture format. Unfortunetly, this Embedded Controller Technology (ECT) course is a compulsory course in any electrical or electronic field of engineering. For this reason, a new laboratory evaluation tool (UMP-EVT) specifically will be designed to be as a learning tool for those who intend to learn microcontroller and for use in the academic environment. By using this UMP-EVT, users are exposed to practical experience of the microcontroller and provide an easy path to learn this intelligent electronic device in short time. In this respect, this UMP-EVT would be applicable for education and expose the electrical engineering students to the understanding fundamental of microcontroller in electronic design field. Keywords: Educational, MCS51 microcontroller, HC11 microcontroller, PIC microcontroller